Effects of long-term antihypertensive treatment on brain metabolism after bilateral carotid artery occlusion in spontaneously hypertensive rats. Issue 12 (December 1979) - Tamaki, K; Fujishima, M; Nakatomi, Y; Ishitsuka, T; Ogata, J; Omae, T
Abstract : The effects of antihypertensive treatment on brain metabolism after bilateral carotid occlusion were studied in spontaneously hypertensive rats. The results indicate that an increase in metabolites of ischaemic brain such as lactate and the lactate/pyruvate ratio after carotid occlusion in spontaneously hypertensive rats is apparently suppressed by treating hypertension. This suggests that hypertension may play an important role in susceptibility to cerebral ischaemia.